Outcomes of SARS-CoV-2 infection in Ph-neg chronic myeloproliferative neoplasms: results from the EPICOVIDEHA registry - Marchetti, Monia; Salmanton-García, Jon; El-Ashwah, Shaimaa; Verga, Luisa; Itri, Federico; Ráčil, Zdeněk; Dávila-Valls, Julio; Martín-Pérez, Sonia; Van Doesum, Jaap; Passamonti, Francesco; Abu-Zeinah, Ghaith; Farina, Francesca; et al. (Therapeutic advances in hematology, 2023)
BACKGROUND: Patients with Philadelphia-negative chronic myeloproliferative neoplasms (MPN) typically incur high rates of infections and both drugs and comorbidities may modulate infection risk. OBJECTIVES: The present study aims to assess the effect of immunosuppressive agents on clinical outcomes of MPN patients affected by the coronavirus disease 2019 (COVID-19). DESIGN: This is an observational study. METHODS: We specifically searched and analyzed MPN patients collected by EPICOVIDEHA online registry, which includes individuals with hematological malignancies diagnosed with COVID-19 since February 2020. RESULTS: Overall, 398 patients with MPN were observed for a median of 76 days [interquartile range (IQR): 19-197] after detection of SARS-CoV2 infection. Median age was 69 years (IQR: 58-77) and 183 individuals (46%) had myelofibrosis (MF). Overall, 121 patients (30%) of the whole cohort received immunosuppressive therapies including steroids, immunomodulatory drugs, or JAK inhibitors. Hospitalization and consecutive admission to intensive care unit was required in 216 (54%) and 53 patients (13%), respectively. Risk factors for hospital admission were identified by multivariable logistic regression and include exposure to immunosuppressive therapies [odds ratio (OR): 2.186; 95% confidence interval (CI): 1.357-3.519], age ⩾70 years, and comorbidities. The fatality rate was 22% overall and the risk of death was independently increased by age ⩾70 years [hazard ratio (HR): 2.191; 95% CI: 1.363-3.521], previous comorbidities, and exposure to immunosuppressive therapies before the infection (HR: 2.143; 95% CI: 1.363-3.521). CONCLUSION: COVID-19 infection led to a particularly dismal outcome in MPN patients receiving immunosuppressive agents or reporting multiple comorbidities. Therefore, specific preventive strategies need to be tailored for such individuals. PLAIN LANGUAGE SUMMARY: EPICOVIDEHA registry reports inferior outcomes of COVID-19 in patients with Philadelphia-negative chronic myeloproliferative neoplasms receiving immunosuppressive therapies. Patients with Philadelphia-negative chronic myeloproliferative neoplasms (MPN) incur high rates of infections during the course of their disease.The present study was aimed at assessing which patient characteristics predicted a worse outcome of SARS-COV-2 infection in individuals with MPN.To pursue this objective, the researchers analyzed the data collected by EPICOVIDEHA, an international online registry, which includes individuals with hematological malignancies diagnosed with COVID-19 since February 2020.The database provided clinical data of 398 patients with MPN incurring COVID-19:Patients were mostly elderly (median age was 69 years);Forty-six percent of them were affected by myelofibrosis, which is the most severe MPN;Moreover, 32% were receiving immunosuppressive therapies (JAK inhibitors, such as ruxolitinib, steroids, or immunomodulatory IMID drugs, such as thalidomide) before COVID-19.Hospitalization was required in 54% of the patients, and the risk of being hospitalized for severe COVID-19 was independently predicted byOlder age;Comorbidities;Exposure to immunosuppressive therapies.Overall, 22% of MPN patients deceased soon after COVID-19 and the risk of death was independently increased over twofold byOlder age;Comorbidities;Exposure to immunosuppressive therapies before the infection.In conclusion, COVID-19 infection led to a particularly dismal outcome in MPN patients receiving immunosuppressive agents, including JAK inhibitors, or reporting multiple comorbidities. Therefore, specific preventive strategies need to be tailored for such individuals.
Keywords: hydroxyurea; myelofibrosis; COVID-19; polycythemia vera; Philadelphia-negative chronic myeloproliferative neoplasms; SARS-CoV-2; ruxolitinib; essential thrombocytemia